PEMANFAATAN MEDIA SOSIAL SEBAGAI STRATEGI KOMUNIKASI PEMASARAN LEMBAGA PENDIDIKAN DI ERA DIGITAL - Ismail Ismail; Na'imah Na'imah (STKIP Pesisir Selatan, 2026)
This study aims to analyze the use of social media as a marketing communication strategy for educational institutions in the digital era through a literature review approach. Developments in information technology have encouraged educational institutions to adapt to modern communication patterns that emphasize interactivity, speed of information dissemination, and effective reach. The study results show that platforms such as Instagram, TikTok, Facebook, and YouTube are widely used to showcase the activities, achievements, and identity of institutions through engaging visual and narrative content. Strategies such as content marketing, storytelling, consistent posting, and active interaction have been shown to increase engagement and build a positive image of the institution. However, the use of social media also faces challenges, including limited digital competency, content inconsistency, privacy ethics issues, and the risk of spreading negative information. Overall, social media has the potential to be an effective marketing tool if managed professionally and in line with educational management principles.